Application of Intelligent Reversing Regulation in Uniform Heating of Buildings - Wu, Xiaoli (Informatica, 2024)
The increase of heating building area makes its energy consumption show an increasing trend, and the manual adjustment method of traditional heating equipment is difficult to adapt to the change of outdoor temperature conditions in time and effectively. Therefore, the control research of heating system with automated intelligent equipment has become an important content to maintain the thermal balance of buildings. Based on this, this study proposes to realize temperature regulation by intelligent commutation in uniform heating of buildings. That is, by identifying the key parameters (energy balance and commutation time ratio) in the process of heating system, the experimental system under the series parallel regulation system is designed, and then the model predictive control under the commutation regulation system is realized with the help of proportional-integral method and particle swarm algorithm. The heating system under this regulation method is tested. The parameter controller can reduce the fluctuation of indoor temperature by adjusting the change of flow rate. The maximum temperature difference is less than 4%, which is much higher than the 7.38% of the traditional algorithm. The intelligent adjustment method can effectively reduce the average heating energy consumption of the building, and the indoor temperature adjustment of the vertical floor is 2°C-3°C lower than that of the manual adjustment mode. This regulation method can provide a good reference value and significance for the northern district heating system to realize effective energy saving and temperature control.